2017
DOI: 10.5920/bjpharm.2017.08
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of co-processed starches prepared by three different methods

Abstract: Co-processing is currently of interest in the generation of high-functionality excipients for tablet formulation. In the present study, comparative analysis of the powder and tableting properties of three co-processed starches prepared by three different methods was carried out. The co-processed excipients consisting of maize starch (90%), acacia gum (7.5%) and colloidal silicon dioxide (2.5%) were prepared by co-dispersion (SAS-CD), co-fusion (SAS-CF) and co-granulation (SAS-CG). Powder properties of each co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Similarly, a study carried out by Wang et al (2015) demonstrated an improvement in the tabletability of lactose when co-processed with hydroxypropyl methylcellulose (HPMC E3) and crospovidone (PVPP). Other studies related to improving the direct compression potential of starches has been achieved by co-processing with binders like acacia [14,15]. In the present study, two co-processed excipients composed of tapioca starch and colloidal silicon dioxide but differing in the binder content were generated by co-fusion.…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, a study carried out by Wang et al (2015) demonstrated an improvement in the tabletability of lactose when co-processed with hydroxypropyl methylcellulose (HPMC E3) and crospovidone (PVPP). Other studies related to improving the direct compression potential of starches has been achieved by co-processing with binders like acacia [14,15]. In the present study, two co-processed excipients composed of tapioca starch and colloidal silicon dioxide but differing in the binder content were generated by co-fusion.…”
Section: Introductionmentioning
confidence: 90%
“…Uniformity in weight of tablets has been attributed to the uniform flow of the formulation mix during the filling of the die leading to compression. This is crucial since poor flow will result in a large range in tablet weight, which could negatively affect the consistency of the tablets' contents and may lead to inconsistent bioavailability of the active ingredient (Apeji et al, 2017).…”
Section: Fourier Transmission Infrared Spectra (Ft-ir)mentioning
confidence: 99%